Emigration and Wages in an Open Economy: Some Evidence from Pakistan (The Pakistan Development Review, 1991)
This paper examines the impact of labour emigration on the wages of both the skilled and unskilled workers. The paper is based on a 3 X 3 trade-theoretic model, where a subset of the goods produced are traded at internationally fIXed prices. The results of the model hinge cruci~y on the intensities of the factors used 'within' the traded goods sectors of the economy. Using the Pakistani data, it is found that unskilled labour is used extremely intensively in the agriculture sector (exportable), skilled labour is used extremely intensively in the manufacturing sector (importable), and capital is used as the middle factor in both the traded goods sectors. Moreover, capital is used significantly less intensively in the construction (non-traded) sector relative to both the traded sectors. Based on the estimated relative factor intensities, the model predicts that emigration of either skilled or unskilled workers from Pakistan, in the long run, would benefit (in nominal as well as real terms) both the skilled and unskilled workers and hurt the owners of capital. The results suggest that the higher wages to both the skilled and unskilled workers must be compensated by a reduction in the rate of returns to capital if export-orientcd and import-competing sectors in Pakistan are to remain internationally competitive.